3, 4, 3′-Tri-O-methylellagic acid as an anticancer agent: in vitro and in silico studies. Issue 46 (19th October 2022) - Wardana, Andika Pramudya; Abdjan, Muhammad Ikhlas; Aminah, Nanik Siti; Fahmi, Mochamad Zakki; Siswanto, Imam; Kristanti, Alfinda Novi; Saputra, Mirza Ardella; Takaya, Yoshiaki
Abstract : We report a natural product compound isolated from Syzygium polycephalum known as 3, 4, 3′-tri- O -methylellagic acid (T-EA) as a candidate drug for cancer treatment using in vitro and in silico approaches. Abstract : We report a natural product compound isolated from Syzygium polycephalum known as 3, 4, 3′-tri- O -methylellagic acid (T-EA) as a candidate drug for cancer treatment. The characterization of the isolated T-EA compound was carried out using various spectroscopic methods. The in vitro evaluation showcased the inhibition activity of T-EA towards the T47D and HeLa cell lines with EC50 values of 55.35 ± 6.28 μg mL −1 and 12.57 ± 2.22 μg mL −1, respectively. Meanwhile, the in silico evaluation aimed to understand the interaction of T-EA with enzymes responsible for cancer regulation at the molecular level by targeting the hindrance of cyclin-dependent kinase 9 (CDK9) and sirtuin 1 (SIRT1) enzymes. T-EA showed a binding free energy towards the SIRT1 protein of Δ G bind (MM-GBSA) : −30.98 ± 0.25 kcal mol −1 and Δ G bind (MM-PBSA) : −24.07 ± 0.30 kcal mol −1, while that of CDK9 was Δ G bind (MM-GBSA) : −29.50 ± 0.22 kcal mol −1 and Δ G bind (MM-PBSA) : −25.87 ± 0.40 kcal mol −1 . The obtained results from this research could be considered as important information on 3, 4, 3′-tri- O -methylellagic acid as a drug to treat cervical and breast cancers.